Realising and compressing quantum circuits with quantum reservoir computing - Sanjib Ghosh (Nature Portfolio, 2021)
Building quantum computers typically requires substantial engineering efforts to achieve precise control on qubits and quantum gates. Here, the authors introduce an architecture based on reservoir computing and machine learning to realize efficient quantum operations without resorting to full optimization of the control parameters.